2011
DOI: 10.1186/1476-511x-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Modification of fatty acids composition in erythrocytes lipids in arterial hypertension associated with dyslipidemia

Abstract: Background: Modification of fatty acids (FA) composition in erythrocytes lipids as an early indicator of the development of arterial hypertension (AH) and lipid disorders. Methods: We included 34 patients with arterial hypertension and 11 healthy individuals. Each patient was examined the lipid composition of serum. From erythrocytes by gas chromatography were identified fatty acids. The quantitative composition of the erythrocyte lipids FA in patients with AH presented with saturated and polyunsaturated monoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Hypertension (AH) and dyslipidemia (DLP) are the most important and frequent risk factors for CVD in the general population, with a prevalence of 50–80% according to different authors [7579]. The prevalence of DLP is 40% among untreated hypertensive patients.…”
Section: Pufas and Cardiovascular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension (AH) and dyslipidemia (DLP) are the most important and frequent risk factors for CVD in the general population, with a prevalence of 50–80% according to different authors [7579]. The prevalence of DLP is 40% among untreated hypertensive patients.…”
Section: Pufas and Cardiovascular Diseasementioning
confidence: 99%
“…Modifications of erythrocyte-membrane fatty acids (FA) composition are an early indicator of the development of AH and lipid disorders [79]. Thus, modifications of erythrocyte-membrane FA are fairly subtle indicators of lipid metabolism pathology which manifest themselves much earlier than changes in plasma lipoproteins.…”
Section: Pufas and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Як засвідчують результати інших досліджень, не менш важливу роль у роз-витку АГ відіграють зміни у складі ЖК не тільки кардіоміоцитів, а й еритроцитів та гладеньком'язових клітин судин. Одержані результати в переважній більшості мають од-накову спрямованість, відрізняючись лише за деякими окремими ЖК [16][17][18].…”
Section: результати та обговоренняunclassified
“…Fatty acids (FAs) are key molecules in living organisms, being involved in several metabolic functions, such as energy storage, membrane structure, signal transduction cascades and protein acylation [1]. In the past three decades, several studies have shown a correlation between the modern western diet, which is considered to be unbalanced due to its richness in n-6 polyunsaturated fatty acids (PUFA) and low levels of n-3 PUFA, and the epidemiology of some chronic diseases, namely cardiovascular diseases [2][3][4][5], diabetes [6][7][8] cell carcinoma [9], Alzheimer's disease [10] and depression [11], among others. Although some epidemiological studies performed so far to evaluate the relation between diet and diseases have relied on data from food frequency questionnaires to assess dietary intake, this approach has several limitations [12].…”
Section: Introductionmentioning
confidence: 99%